RICHMOND HEALTH AND WELLNESS PROGRAM: COMMUNITY ADVISORY COUNCIL OUTCOMES. (11th November 2018) - Zanjani, F; Falls, K; McQueen Gibson, E; Patel, K; Price, E; Sargent, L; Slattum, P; Parsons, P
Abstract: The Richmond Health and Wellness Program (RHWP) provides interprofessional care coordination and wellness services within Richmond's low income senior housing communities for approximately 1, 000 subsidized housing units. As part of the RHWP mission, an Advisory Council was developed, to address community concerns around race and culture, and to advance social equity as an integral dimension of program sustainability. The Advisory Council meets quarterly to ensure the community's voice is integrated into RHWP sustainable programming of research and service. Residents from the housing buildings and surrounding community were recruited to comprise the Council. Attendance at the Advisory Council is supported through meal and transportation accommodations. Two Council meetings were used to identify health themes, these included: diabetes, health education, hepatitis C, healthy food access, mental health, men's/women's health, predatory senior practices (fraud), opioid epidemic, sex education, safety/emergency preparedness, and community public service access. Council members expressed a need for research on the follow themes: addiction, cognitive decline, environmental stressors, and polypharmacy. A subsequent Council meeting addressed the theme for resident mental health needs with an educational presentation and connection with the local National Alliance for Mental Illness chapter and initiating a Diabetes management program in the residential units. In conclusion, themes from the Advisory Council meetings were identified and used to advance resident health and RHWP programming. This RHWP approach has opened doors to older adults living within subsidized housing units, to identify their prominent health needs and mutual opportunities for engagement and improvement toward successful aging.